2019
DOI: 10.1024/0300-9831/a000255
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary intake of some antioxidant micronutrients with some inflammatory and antioxidant markers in active Rheumatoid Arthritis patients

Abstract: Abstract. Background: Rheumatoid Arthritis (RA) is an autoimmune disease. Antioxidants intake and body antioxidants status are important in patients with RA. The aim of this study was to investigate the association between dietary intake of some antioxidant micronutrients with some inflammatory and antioxidant markers in patients with active rheumatoid arthritis and comparison with Recommended Dietary Allowance (RDA). Materials and Methods: In this cross-sectional study, eighty-seven patients with active rheum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…19 In addition, a cross-sectional study also showed that magnesium intake in patients with RA was significantly lower than the Recommended Dietary Allowance (RDA) (320 mg/day), and negative correlations were observed between magnesium intake and RA. 15 However, other studies stated conflicting results that provided non-significant associations between magnesium intake and RA. 36 37 On the whole, we consider that the reasons for these contradictory results may involve Figure 2 The non-linear correlation between dietary magnesium intake and prevalence of rheumatoid arthritis (RA) in women (using penalised spline method).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In addition, a cross-sectional study also showed that magnesium intake in patients with RA was significantly lower than the Recommended Dietary Allowance (RDA) (320 mg/day), and negative correlations were observed between magnesium intake and RA. 15 However, other studies stated conflicting results that provided non-significant associations between magnesium intake and RA. 36 37 On the whole, we consider that the reasons for these contradictory results may involve Figure 2 The non-linear correlation between dietary magnesium intake and prevalence of rheumatoid arthritis (RA) in women (using penalised spline method).…”
Section: Discussionmentioning
confidence: 99%
“…13 14 Therefore, there are reasons to suspect the role of dietary magnesium intake in women with RA. Research on the relationship between magnesium and RA is limited and controversial, [15][16][17][18] with even fewer studies on women. According to a Pakistani study, women with RA had lower levels of magnesium in their blood, serum and hair.…”
mentioning
confidence: 99%
“…A study conducted in Iranian women with established RA reported that there was a consumption higher than the Dietary Reference Intakes (DRIs) of Se (87.7 ± 56.2 µg/day); in this study, only 26% of the sample did not reach DRIs of Se [ 49 ]. Likewise, another study carried out in Iran also reported higher Se consumption than DRIs, which also showed a negative correlation with prostaglandin E 2 levels (R = −0.21; p =< 0.05) [ 50 ]. In contrast to these results, a study conducted in New Zealand reported that RA patients had a consumption of 36 ± 21.9 µg/day of Se.…”
Section: Nutritional Selenium Status In Rheumatoid Arthritismentioning
confidence: 94%
“…Nevertheless, these tools for evaluating habitual food consumption are still some of the most appropriate for this type of study. It is also important to say that most of the studies mentioned here did not have a comparison control group [ 49 , 50 , 51 , 52 , 54 , 56 ]. In contrast, there are also studies in which the consumption of Se can be overestimated, and this could be due to the fact that patients with previous knowledge of the recommended foods could over-report their consumption.…”
Section: Nutritional Selenium Status In Rheumatoid Arthritismentioning
confidence: 99%
“…The dietary intake of vitamin E was associated by Arablou and colleagues with higher catalase enzyme activity [102]. Independently to its antioxidant properties, the α-tocopherol, although dose-dependent ranging from 10 to 50 μM, has been shown to be able to inhibit protein kinase C activity [103].…”
Section: Vitamin Ementioning
confidence: 99%